Pelatihan Desain Grafis Pembuatan Flyer Produk Untuk Promosi Konten Media Sosial - Ibnu Rusdi; Supriyadi; Ade Christian; Indah Suryani (Jurnal Pengabdian Masyarakat Akademisi, 2022)
The Covid-19 pandemic is an event that spreads the corona virus disease 2019 (Coronavirus Disease 2019) throughout the world. In response to this pandemic, the government has implemented various policies to limit the movement of people to suppress the spread of the Covid-19 virus in Indonesia. One aspect that has changed, due to the Covid-19 pandemic, is the way humans survive because of the many closures by trading offline. This impact was also felt by women who were members of the Fatayat NU (Nahdlatul Ulama) Ciledug organization. Fatayat NU is an Islamic women's organization which is one of the autonomous institutions within NU, which is religious, social and familial. The concept of Fatayat NU activities can be classified into three, namely in the field of regeneration and education, the field of da'wah or Islamic development, and the field of social society. One of these activities is closely related to government programs through the empowerment of MSMEs. The problems faced by Fatayat NU Ciledug, relating to the empowerment of MSMEs are: (1) Lack of knowledge to use social media in terms of publishing business; and (2) Lack of skills in using and processing graphic design applications to create flyers in order to promote their business. The solutions offered to solve these problems are through this community service activity, namely providing online training/workshops by utilizing social media to members of Fatayat NU Ciledug.